EFFECTIVENESS OF CONTINUOUS ASSESSMENT LEARNING ACTIVITIES (CALA) BY THE MINISTRY OF PRIMARY AND SECONDARY EDUCATION IN NYANGA DISTRICT, ZIMBABWE - Juet Nyamudzodza; Admire Mthombeni; Shingirai Siziva; Obert Sifile; Faitira Manuere (The University of Kuningan, 2021)
The study sought to determine the effectiveness of the implementation of Continuous Assessment Learning Activities (CALA) by the Ministry of Primary and Secondary Education in Nyanga, Zimbabwe. The researchers were motivated to carry out the research due to the endless outcry by students who are finding CALA difficult to execute and teachers who are also finding it difficult to guide the students. The initiative was introduced by the Ministry of Primary and Secondary Education arguably without proper planning and budgeting, which has so far affected the implementation process. The researchers adopted an exploratory research approach to understand the key factors that have impacted on the implementation of Continuous Assessment Learning Activities (CALA) in Zimbabwe. A qualitative research approach was used by the researcher through the use of questionnaires as a data collection instrument for the research. A total of 35 questionnaires were distributed to both the students and teachers from various schools in Nyanga District in Manicaland and a response rate of 94% was yielded. The results indicate that the decision to introduce continuous assessment activities in secondary schools was noble, but it was negatively affected by a number of controllable factors. The findings of the study also showed that there was poor planning by the Ministry of Primary and Secondary Education in the implementation of CALA, which has led to students’ outcry. The researchers recommended the involvement of teachers in the decision making process as they are the implementers of the initiative. The importance of teachers in the process should not be overlooked as they are the gatekeepers who play an important role in the success of this noble initiative.Keywords: Continuous Assessment, Teacher Motivation, Secondary Education, Primary Education